(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2015)
This paper analyzes terminally ill patient’s fundamental rights. It examines, in first instance, the right to life and to die with dignity from a constitutional perspective; then, it investigates medical ethics standard’s as ruled by Brazilian Federal Council of Medicine in the last ten years, especially those about the right to information and patient’s consent or refusal to undergo medical treatments and living wills. Finally and from the perspective of patients fundamental rights, the paper deals with the Criminal Code project currently under discussion in the Brazilian Congress, which aims to criminalize euthanasia.